E-SIM: SMARTCARD RFID SEBAGAI PENGAMANAN MOBIL DAN PENCEGAHAN PENGEMUDI DI BAWAH UMUR - Faizin, Arrizal; Khairunnisa, Nurul; Nurdiana, Norma (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Traffic accident affects the under age driver. The purpose of making this tool is to create a design, knowing the process, and applying of E-SIM (Electronics-SIM) based on RFID smartcard as an effort to achieve security of car and to solve the misapplication of driver under age. The methods used are the concept design, the creating of tool, and the applying of tool. This tool uses input of RFID of RDM6300 reader with the frequency of around 125 KHz. The process of this tool uses ATmega 16 micro-controller system and the output of this tool consists of relay for controlling the contact. All systems make it into one tool and placed in the dashboard of the car. From this result, this tool has the best performance.